Mixed Method Strategies to DevelopThe Acquisition of ESP Students’ Skills of on Line Marketing - Bakhrul Khair Amal; Muhammad Natsir; Supsiloani Supsiloani; Rita Suswati (BIRCU, 2019)
English for Spesific purposes is one of the topicthat hold a great deal of advantages for students in Literature program. It aims to give a chance to the students to feel the working environment and see how it will be when they want to get involve into the bussiness. The variety jobs have been offered to youngsters but the most current opportunity is on line bussiness. It opens a wide range of chance for students to achieve. In order to do so, students should master some skills, not only pedagogic skills but also marketing skills. This research tries to answer the question of how to acquire ESP students’ skillsof online marketing using mixed method, consist of qualitative, quantitative into a mixed method research approaches. The population is the senior students who are going to do field observations in several offices, consists of 30 students of english literature department program. The results show that; (1) Mixed Methods has a significat impact on the acquisition of ESP students’ skills ofon line marketing, (2) online marketing is still a prosperous bussiness for the future. Further it is suggested to do more research on this area to enrich the knowledge of online bussiness as one of the new option of profession for students of english literature department program in FBS Universitas Negeri Medan (UNIMED).